Pathological differences between clinically suspected and unsuspected gallbladder carcinoma: A 5- year retrospective study - Dr. Prabir Hazarika; Dr.Rasadhar Deka; Dr. Manoj K Sharma (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Gallbladder carcinoma frequently presents as incidental finding in routine cholecystectomy specimens operated for gallstone diseases. The reason behind unrecognition of these tumors pre and intraoperatively and its significance need evaluation. Objective: We have done a 5 years retrospective study from December 2011 to November 2016 in a referral centre to evaluate the pathological features of unsuspected gallbladder carcinoma and to compare these with those of suspected carcinomas. Methods: A total record of 74 cases of gallbladder carcinomas are retrieved from the archives. These are 54 whole gallbladder specimens of simple and extended cholecystectomies and 24 small tissue pieces of gallbladder. Out of 54 whole gallbladder specimens 30 are clinically unsuspected and 24 are suspected carcinomas. Result: Majority of the unsuspected group have diffusely thickened gallbladder wall as their sole gross presentation or no grossly identifiable lesion at all. On the other hand, suspected gallbladder carcinomas have presented mostly as localized wall thickening, thickened wall with invasion of the adjacent structures or large intraluminal mass. Adenocarcinoma was the commonest histological type in suspected and exclusive type in unsuspected group. Most of the unsuspected carcinomas are well differentiated in contrast to the suspected carcinomas which are mostly poorly differentiated followed by almost equal prevalence of moderately differentiated and well differentiated tumors. Half of the unsuspected tumors are limited to gallbladder and no cases of pT4 stage are present. On the contrary, only one fourth of cases of the suspected carcinomas are limited to gallbladder and another one fourth are in pT4 stage. Conclusion: Unsuspected gallbladder carcinoma show different gross presentation and also tend to be better differentiated and in earlier stages than suspected carcinomas.